2021
DOI: 10.3390/jcm10225447
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Preoperative Serum Levels of Calcium, Phosphate, and Intact Parathyroid Hormone and Radiological Outcomes in Spinal Interbody Fusion among End-Stage Renal Disease Patients

Abstract: Spinal fusion surgery for end-stage renal disease (ESRD) patients is a clinical challenge. This study aimed to investigate whether postoperative radiological outcomes are related to preoperative serum calcium, phosphate, or intact parathyroid hormone (iPTH) levels in patients with ESRD who underwent spinal interbody fusion surgery. This study included 62-consecutive patients with ESRD who underwent anterior cervical discectomy and fusion (ACDF) or transforaminal lumbar interbody fusion (TLIF) surgery for sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A fascinating finding was that although CHD was negatively associated with severe disc degeneration, the effect of CHD on disc degeneration was not significant in models with only CHD and calcification. Furthermore, this study showed that preoperative high serum phosphorus levels were associated with fusion rate, while Shih et al found no correlation between the fusion rate and the serum levels of calcium or phosphorus [ 43 ]. Additionally, we note that UA can enhance fusion rate, which may be related to its antioxidant abilities.…”
Section: Discussionmentioning
confidence: 99%
“…A fascinating finding was that although CHD was negatively associated with severe disc degeneration, the effect of CHD on disc degeneration was not significant in models with only CHD and calcification. Furthermore, this study showed that preoperative high serum phosphorus levels were associated with fusion rate, while Shih et al found no correlation between the fusion rate and the serum levels of calcium or phosphorus [ 43 ]. Additionally, we note that UA can enhance fusion rate, which may be related to its antioxidant abilities.…”
Section: Discussionmentioning
confidence: 99%